THE CONCEPT OF FOREIGN POLICY : A STUDY OF MEANS AND ENDS - شمبش, علي (Dirasat in Economics and Business, 1975)
This article attempts an explanation of the concept of foreign policy within the frame of means and ends. The reason for such an analysis is that every foreign policy decision is taken and executed within the available means and pursued ends. Therefore, some comprehensive understanding for those mean and ends would make the interested person comprehend why a certain country behaves in a particular manner. Moreover, this person would understand different countries actions and reactions in the international arena. This article, as a study of means and ends in foreign policy, discusses the general means of diplomacy, foreign aids, blocs, and war. It also discusses the general ends of protecting national independence, assuring territorial safety, and pursuing regional or international power.